KINERJA PEREKONOMIAN KABUPATEN PONTIANAK - B61111033, IDA RUSTIANTI (Jurnal Ekonomi Daerah (JEDA), 2014)
ABSTRACT This study has the following objectives: 1) to determine the occurrence of regional economic growth in Pontianak district by using the Shift-Share analysis. 2) To determine the role of economic sectors in Pontianak regency on the economy of West Kalimantan my by using the LQ analysis. 3) To determine whether the optimum of the performance of the economy in Pontianak regency has been able to run optimally or not based on the Klassen typology criteria. This study uses secondary data derived from Sectored Product Domestic Regional Bruto (PDRB)Â of West Kalimantan Province and Pontianak District from 2007-2011. This study used a descriptive quantitative approach and explorative study. As to determine what sectors are identified as the leading sectors and to map and formulate the development strategy of the regionsâ€™ potential economic sector, the following analytical methods may be used: 1) Klassen typology Analysis, 2) Shift-Share Analysis (SSA) and 3) Analysis of Location Quotient (LQ). The research results which were drawn as a synthesis of this study are as follows: 1) The economic growth in west Kalimantan province experienced the largest increase from 2007 to 2008 which was able to reach at 15.67%. This shows that in the period of 2007-2008 there had been maximization in the sectors sought by West Kalimantan province, especially in agricultural sector, typically in the export and import activities consisting of the sub sectors of food crops, plantation and fisheries. While the economic growth of Pontianak district experienced the largest increase from 2007 to 2008 that was capable of achieving at 14.61%. 2) based on the shift share analysis component, it is found that the economic sector components considered to be competitive in Pontianak regency in the period of 2007 to 2011 are agriculture and electricity, gas, and water. 3) based on the results of the Klassen Typology Analysis, it is foundÂ that if viewed from the economic sector contribution in terms of economic growth in the economic sector, especially in Pontianak regency, it can be seen that the Agricultural sector and the electricity, gas, and water are the primary sectors. 4) based on the analysis of LQ on economic sectors in Pontianak regency, the potential sectors in the district are agriculture and the service sectors. keywords: optimal, sectored performance, the sectored role, industrial competitiveness, Product Domestic regional Bruto (PDRB)